Teacher's Feedback Technique In Teaching Descriptive TextTo The Eight Grade Students Of SMP N 2 Banyudono In 2016/2017 Academic Year - Sekarsari, Giandira, Mauly Halwat Hikmat, Ph.D (2017)
This study is aimed at describing: 1) the teacher feedback technique used in teaching writing descriptive text, and 2) the problems faced by the teacher in teaching descriptive text using teachr feedback technique. In achieving the objectives, the researcher used descriptive qualitative as an approach to collect and analyze the data. The research was held in SMP N 2 Banyudono. The research took 34 students of the second year students as the subject of the study. The researcher gets the data of the research from event, informant, and document. The techniques for collecting data are observation, interview, and document analysis. The result of the analysis shows that the teacher corrective feedback techniques are appropriate and effective to the eight grade students of SMP N 2 Banyudono in teaching descriptive text. By using this technique, the students are capable of knowing errors, the reason and corret it. So, it can facilitate the teaching-learning process. The teacher has several problems in teching namely the students difficulties in finding the theme, students difficulties in developing the content, the students difficulties in understanding the components of writing, and the deficiency of teaching media.